2023
DOI: 10.1007/s41649-023-00241-w
|View full text |Cite
|
Sign up to set email alerts
|

Poor Representation of Developing Countries in Editorial Boards of Leading Obstetrics and Gynaecology Journals

Abstract: Evidence suggests a limited contribution to the total research output in leading obstetrics and gynaecology journals by researchers from the developing world. Editorial bias, quality of scientific research produced and language barriers have been attributed as possible causes for this phenomenon. The aim of this study was to understand the prevalence of editorial board members based out of low and lower-middle income countries in leading journals in the field of obstetrics and gynaecology. The top 21 journals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Additionally, they are better positioned to advocate for implementing the research findings [ 44 ]. However, conducting research in LMIC differs significantly from HIC [ 45 , 46 ]. Many clinicians in LMIC do not have dedicated time for research due to heavy clinical workloads [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, they are better positioned to advocate for implementing the research findings [ 44 ]. However, conducting research in LMIC differs significantly from HIC [ 45 , 46 ]. Many clinicians in LMIC do not have dedicated time for research due to heavy clinical workloads [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, conducting research in LMIC differs significantly from HIC [ 45 , 46 ]. Many clinicians in LMIC do not have dedicated time for research due to heavy clinical workloads [ 45 ]. Furthermore, there are barriers that restrict access to current scientific literature for authors and readers in LMIC [ 41 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence from smaller decision-making committees highlights that increased representation of women in leadership facilitates better representation of women in a committee, as noted in a study from the United States of America where it was observed that the proportion of women on the board of directors was higher when the chairperson was a woman [ 8 ]. Increased women representation is also important to ensure that a diverse range of issues is addressed by a committee [ 9 ]. Reduced diversity in terms of gender, race, and ethnicity is a problem that plagues committees formulating clinical guidelines as well.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the location and experience of the decision-maker also play a significant role [ 11 ]. Although direct evidence of the impact of diversity of representation on policy formulation is limited, inference can be drawn from the similar impact of poor diversity seen in the world of academia [ 12 ]. Diverse representation has also been shown to improve the outcome of teams [ 13 ], better equipping them to handle inequities in health [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%